The Effects of Electromagnetic Articulography Sensors on Speech in Individuals With and Without Parkinson's Disease. - Thompson, Austin; Hirsch, Micah; Kim, Yunjung (Journal of Speech, Language & Hearing Research, 2026)
Purpose: This study examined how wearing electromagnetic articulography (EMA) sensors affects acoustic and perceptual speech outcomes in people with Parkinson's disease (PwPD) with dysarthria and neurologically healthy control speakers. Additionally, the study explored potential after-effects on acoustic and perceptual measures following approximately 45 min of wearing EMA sensors in both groups. Finally, we investigated whether wearing EMA sensors or after-sensor effects differentially impacted the two groups. Method: Thirty-four speakers (21 controls and 13 PwPD) read "The Caterpillar" passage at three time points: (a) before sensors, (b) with sensors, and (c) after sensors. We analyzed changes in acoustic (articulation rate, articulatory--acoustic vowel space [AAVS], first and second spectral moment coefficients for fricatives) and perceptual (speech intelligibility, naturalness) measures across two key contrasts: sensor effects (With Sensors -- Before Sensors) and after-sensor effects (After Sensors -- Before Sensors). Results: Bayesian linear mixed-effects models showed sensor effects (With Sensors -- Before Sensors), with EMA sensors reducing intelligibility and naturalness and altering fricative spectral moments in both groups. Additionally, control speakers exhibited a faster articulation rate with sensors. Notably, PwPD were more negatively impacted by sensor effects in terms of intelligibility ratings. After-sensor effects (After Sensors -- Before Sensors) were also observed: Control speakers spoke faster following sensor removal, while PwPD demonstrated increased AAVS and were perceived as more natural. However, there was no compelling evidence that after-sensor effects differed between groups. Conclusions: EMA sensors primarily impact sibilant fricative production and perceptions of intelligibility and naturalness in PwPD and control speakers. PwPD experience greater sensor-related reductions in intelligibility, which should be carefully considered when using speech data collected with EMA to assess perceptual measures in clinical populations. Finally, PwPD exhibited increased naturalness and greater spectral distinctiveness following sensor removal, which we speculate may stem from increased passage familiarity and reduced cognitive demand. Supplemental Material and Open Science Form: https://doi.org/10.23641/asha. 31052272